The garlic ballads - Mo, Yan 1956- (Viking, 1995)
In China, the tragic romance of farmer Gao Ma and Fang Jijnu, the pregnant woman who elopes with him. It is told against the background of the 1988 garlic farmers' revolt, protesting corrupt officialdom in Paradise County. By the author of Red Sorghum.
Keywords: China -- Fiction; Fiktionale Darstellung; Political fiction